Weaving relationships between “body techniques” and “self-care” - Mendes, Maria Isabel Brandão de Souza (Frontiers in Sociology, 2025)
Epistemological questioning is necessary for any knowledge area because it brings up reflections on its foundations. The objective of this article is to understand the relationships between studies on “body techniques” and “self-care.” This is a bibliographical study on the relationships between “self-care” and “body techniques” based on the studies of Foucault and Mauss and based on updated articles on these concepts. We situate the context in which the notion of body techniques and then the notion of self-care emerge. We subsequently correlate the classification of body techniques developed by Marcel Mauss and establish relationships with the possibilities of self-care. Next, we identify that many body techniques are part of the practices of the regime, which have existed since the Socratic-Platonic moment in our Western society. We point out that Physical Education/Sports Science has a crucial importance in teaching self-care. We emphasize that professionals in this knowledge area can open spaces for reflection on body techniques which contribute to self-care and do not dictate norms, as subjects are capable of making choices based on their learning.